Tobacco Use and Related Factors Among Women in Aydın, Turkey: A Mixed Study - Köksal Yasin, Yağmur; Okyay, Pınar (Addicta: The Turkish Journal on Addictions, 2023)
Today, one of the most important targets of the tobacco industry is women. Despite the programs implemented so far in the world, the desired success has not been achieved in tobacco use. The aim of our study was to determine the prevalence of tobacco use among women in Aydin and to evaluate the tobacco use experience. The quantitative phase was cross-sectional research design, while the qualitative phase employed a phenomenological design. In the quantitative phase, 1577 people were reached. The qualitative phase was conducted with 45 women smoking tobacco, 2 with their relatives, and 10 public health professionals. The frequency of tobacco use is 23.2%. Smoking status was found to be higher in those aged 44 and under, widowed/divorced, university or higher education level, employed, and living in urban areas. Six main themes related to tobacco use in women were determined in the qualitative phase: “Tobacco control policies,” “Starting smoking process,” “Individual effect of smoking,” “Smoking process,” “Smoking cessation process,” and “Root causes and holistic approach.” In the fight against tobacco use in women, it is important to eliminate gender inequality, empower women, increase social welfare, global struggle, and ensure the wellbeing of society.